Kehamilan Dini Remaja Kristen: Upaya dan Evaluasi Pendampingannya di Rumah Singgah Griya Welas Asih Semarang - Minggus Minggus; Rosalia Amaya (Journal Of Social Empowerment Publications, 2024)
Researchers intend to understand the reasons behind the phenomenon of teenagers experiencing early pregnancy outside of official marriage and provide assistance. How teenagers struggle with self-acceptance and what efforts they make to overcome the tension: between discomfort on the one hand and the urgent need to adapt to environmental demands. Assistance is carried out by means of observation and interviews. There were 10 Christian teenagers who were accompanied, aged 12-19 years, unmarried, pregnant, and domiciled in the city of Semarang, as well as several cities in Central Java. The results of the assistance showed that the ten teenagers had gone through a period known as a chaotic period, where they felt embarrassed, afraid, confused, and even had the desire to abort their pregnancies. This can be overcome with the support provided by family and close friends. On the other hand, this activity emphasizes the importance of measurable and sustainable assistance so that teenagers have a better perspective and attitude in life than before.